Umbilical Cord Abnormalities and Stillbirth. Issue 3 (March 2020) - Hammad, Ibrahim A.; Blue, Nathan R.; Allshouse, Amanda A.; Silver, Robert M.; Gibbins, Karen J.; Page, Jessica M.; Goldenberg, Robert L.; Reddy, Uma M.; Saade, George R.; Dudley, Donald J.; Thorsten, Vanessa R.; Conway, Deborah L.; et al.
Abstract : OBJECTIVE: Umbilical cord abnormalities are commonly cited as a cause of stillbirth, but details regarding these stillbirths are rare. Our objective was to characterize stillbirths associated with umbilical cord abnormalities using rigorous criteria and to examine associated risk factors. METHODS: The Stillbirth Collaborative Research Network conducted a case-control study of stillbirth and live births from 2006 to 2008. We analyzed stillbirths that underwent complete fetal and placental evaluations and cause of death analysis using the INCODE (Initial Causes of Fetal Death) classification system. Umbilical cord abnormality was defined as cord entrapment (defined as nuchal, body, shoulder cord accompanied by evidence of cord occlusion on pathologic examination); knots, torsions, or strictures with thrombi, or other obstruction by pathologic examination; cord prolapse; vasa previa; and compromised fetal microcirculation, which is defined as a histopathologic finding that represents objective evidence of vascular obstruction and can be used to indirectly confirm umbilical cord abnormalities when suspected as a cause for stillbirth. We compared demographic and clinical factors between women with stillbirths associated with umbilical cord abnormalities and those associated with other causes, as well as with live births. Secondarily, we analyzed the subset of pregnancies with a low umbilical cord index. RESULTS: Of 496 stillbirths with complete cause of death analysis by INCODE, 94 (19%, 95% CI 16–23%) were associated with umbilical cord abnormality. Forty-five (48%) had compromised fetal microcirculation, 27 (29%) had cord entrapment, 26 (27%) knots, torsions, or stricture, and five (5%) had cord prolapse. No cases of vasa previa occurred. With few exceptions, maternal characteristics were similar between umbilical cord abnormality stillbirths and non–umbilical cord abnormality stillbirths and between umbilical cord abnormality stillbirths and live births, including among a subanalysis of those with hypo-coiled umbilical cords. CONCLUSION: Umbilical cord abnormalities are an important risk factor for stillbirth, accounting for 19% of cases, even when using rigorous criteria. Few specific maternal and clinical characteristics were associated with risk. Abstract : Although 19% of stillbirths were attributable to umbilical cord abnormalities in a diverse U.S. cohort, few clinical characteristics were associated with useful risk factors.